Kalkulator Hijau Self-Assessment: Solusi Inovasi atas Evaluasi Praktik Taksonomi Keuangan Berkelanjutan di Indonesia - Silvia Rahmawati; Naila Maulidya Rahma; Adib Naufal Musthofa (Universitas Muhammadiyah Palembang, 2025)
Green taxonomy is a guideline for classifying companies in carrying out economic activities according to ESG regulations that impact funding. However, the transition from Taxonomi Hijau Indonesia (THI) to Taksonomi Keuangan Berkelanjutan Indonesia (TKBI) has made the classification more ambiguous. Additionally, this program remains voluntary, involves self-assessment, and lacks third-party verification, increasing the potential for greenwashing. This study aims to provide recommendations for optimizing the implementation of the green taxonomy in Indonesia to reduce the subjectivity of company classification. Using a qualitative descriptive method and comparative study, this research compares the implementation of the green taxonomy in the European Union, which already has third-party-based classification tools. The researcher proposes a Self Assessment Calculator based on TKBI to reduce bias, inspired by the EU Taxonomy Calculator. Moreover, this study examines recommendations for a more comprehensive form of TKBI in line with the MECE principle through global best practice analysis and pentahelix stakeholder synergy